2020
DOI: 10.3762/bjoc.16.34
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric ricinoleic acid preparation promoted by an efficient and recoverable Brønsted acidic ionic liquid

Abstract: Raw material from biomass and green preparation processes are the two key features for the development of green products. As a bio-lubricant in metalworking fluids, estolides of ricinoleic acid are considered as the promising substitute to mineral oil with a favorable viscosity and viscosity index. Thus, an efficient and sustainable synthesis protocol is urgently needed to make the product really green. In this work, an environment-friendly Brønsted acidic ionic liquid (IL) 1-butanesulfonic acid diazabicyclo[5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In the previous work from our research group, it was found that Tin(II) oxide (SnO) presented excellent catalytic activity for the synthesis of oligomeric ricinoleic acid through an intermolecular esterification reaction of ricinoleic acid (You et al, 2020). In this work, the catalyst SnO was applied to the preparation of polyol ricinoleates via the esterification reaction of ricinoleic acid and polyols including trimethylolpropane (TMP), pentaerythritol (PE), and neopentyl glycol (NPG) in the presence of dehydrant.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous work from our research group, it was found that Tin(II) oxide (SnO) presented excellent catalytic activity for the synthesis of oligomeric ricinoleic acid through an intermolecular esterification reaction of ricinoleic acid (You et al, 2020). In this work, the catalyst SnO was applied to the preparation of polyol ricinoleates via the esterification reaction of ricinoleic acid and polyols including trimethylolpropane (TMP), pentaerythritol (PE), and neopentyl glycol (NPG) in the presence of dehydrant.…”
Section: Introductionmentioning
confidence: 99%